SEYAHATNAMELERDE BAĞDAT - GÜLER, BÜŞRA (Fırat Üniveristesi, 2018)
Abbasîler dönemi, İslam şehri ve mimarisi açısından en önemli ve verimli dönemlerden birini teşkil etmektedir. Bu dönem İslam şehirciliği için olgunluk devri olarak ifade edilmektedir. Nitekim Müslüman coğrafyadaki şehirleşme temayülü iyice açığa çıkmış ve çok sayıda şehir kurulmuştur. Özellikle Abbasîlerin ilk asrında kurulan şehirler, hem sayı hem de nitelik bakımından İslam tarihinin diğer devirlerine göre üstünlük arz etmektedir. Güvenli başşehir arayışıyla başlayan ve her halifenin kendi adıyla anılacak şehirler kurma isteklerinin etkisiyle gelişen şehirleşme faaliyeti, İslam medeniyet tarihinde iz bırakan çok sayıda şehrin ortaya çıkmasını sağlamıştır. Kuruluşu kadim dönemlere uzanan Bağdat şehri de bu süreçte yeniden canlanmış ve eski parlak günlerine kavuşmuştur. Abbasîler devrinde, doğusundan batısına kadar ülkenin bütün bölgelerinde inkişaf eden şehircilik faaliyetinin en yoğun olduğu yer, devletin idarî merkezi durumunda olan Irak'tır. Bu çerçevede Abbasîlerde şehircilik denilince ilk akla gelen kent ise Bağdat'tır. Buna bağlı olarak aşağı ve yukarı Mezopotamya bölgesinde Bağdat'ın dışında irili ufaklı birçok şehir kurulmuştur. Hz. Ömer döneminde H. 13/M. 634 yılında Müsennâ b. Hârise tarafından fethedilen Bağdat, Dört Halife dönemi boyunca ticarî faaliyetlerin devam ettiği bir şehir olmuş, Emeviler döneminde daha çok askerî bir karargâh olarak benimsenmiştir. Ancak Bağdat Halife Mansur dönemiyle birlikte önemli bir konuma sahip olmuş ve şehircilik alanında temayüz etmiş bir şehirdir. Nitekim Halife Mansur zamanına gelindiğinde, Abbasî halifeliği için yeni bir merkez inşası gündeme gelmiştir. Bu noktada yapılan araştırma sürecinde Halife Mansur idarî, siyasî ve ekonomik açıdan önemli ve stratejik bir yere yeni merkezi kurmayı istemiştir. Çünkü Kûfe yakınlarındaki Hâşimiyye'de kalan Mansur, Hz. Ali taraftarı olan Kûfe şehrine yakın olmanın ordusu üzerinde olumsuz bir etki bırakacağını anlamış ve daha uygun bir yer aramaya başlamıştır. Aramış olduğu bu şehir "Medinetü's-selam" ismiyle anılacak olan Bağdat olmuştur. Şehri merak eden seyyahlar Bağdat'ı gezmişler ve sosyal, kültürel yapısını da seyahatnamelerinde anlatmışlardır. Seyahatnameler şehir tarihlerinin başlıca kaynakları arasında yer almıştır. Özellikle Abbasîler, Selçuklular ve Osmanlı Devletleri idaresinde bulunan Bağdat'ı merak eden veya değişik amaçla bölgeye gelenler arasında seyyahlar da bulunmaktadır. Arabistan, İran, Anadolu ve Avrupa'dan gelip buranın özelliklerini ele alan seyahatname yazarlarının verdikleri bilgiler ilgi çekmektedir. Dolayısıyla Bağdat'ı çeşitli yönleriyle anlatan seyyahların gözüyle tanımak önem arz etmektedir. Biz bu çalışmamızda Abbasî hilafetinin başkenti ve İslâm dünyasının önemli tarih, ilim, kültür, siyaset ve ticaret merkezlerinden olan Bağdat şehrini seyahatnamelerde anlatmaya gayret göstereceğiz. İslâm öncesi ve İslam sonrasındaki tarihi yapısı ve günümüze kadarki süreçte Bağdat'ın geçirmiş olduğu değişimler üzerinde duracağız.

The Abbasid period constitutes one of the most significant and productive stages in terms of the concept of Islamic city and its architecture. This period is deemed as the period of maturity for the Islamic urban planning. During this era, urbanization tendency in the Islamic geography completely became prominent, and many cities were established. Especially the cities founded in the first century of the Abbasids are superior in both quantitative and qualitative manners compared to other periods of the Islamic history. Urbanization activities, which started with the seeking for a safe capital city and which developed by the inspirations of each caliphates' desires to establish a city to be known with their names, have led to the emergence of many cities that have left an impression on the history of Islamic civilization. The city of Baghdad, whose establishment dates back to the ancient times, revived during this period, and regained its palmy days as it was in the past. During the Abbasid Period, it was Iraq, the administrative center of the state, where the urbanization activity was at the highest rate and developed in all regions of the country from the east to the west. In this context, Baghdad is the first city that spring to mind when the subject is urbanism in the Abbasids. Accordingly, many large and small cities in Upper and Lower Mesopotamia were established in this region apart from Baghdad. Baghdad, conquered by Al-Musannah bin Harisah during the Caliph Umar in 634 A.D (in 13 A.H, according to the hijri calendar), became a city where the commercial activities continued throughout the Rashidun Caliphate [the Era of the Four Caliphs], and was mostly used as a military base during the Umayyad Period. Yet, Baghdad is a city that came to the fore with the Era of the Caliph Al-Mansur, and rose to prominence in the field of urbanism. As a matter of fact, the establishment of a new center for the Abbasid Caliphate was brought to the agenda when it came to the period of the Caliph Al-Mansur. At this point, the Caliph Al-Mansur wanted to establish the new center in an administratively, politically, economically and strategically important region. Because al-Mansur, who was in al-Hashimiyyah near Kufa, realized that being close to the city of Kufa, where was full of the Caliph Ali's supporters, would have had a negative effect on his army; and thus he began to search for a more suitable place. The city he had sought out was Baghdad, which would be called Mad?nat as-Sal?m [that means 'The City of Peace']. Travelers wondering about Baghdad made journeys to this city, and narrated its social and cultural structure in their travel books (Seyahatname). Travel books have been among the main sources of city histories. There are travelers among those who especially wonder about Baghdad under the rules of Abbasids, the Seljuks, and Ottoman States throughout history, or those who came to the region for different purposes. The information given by the writers of these travel books, who had come from Arabia, Iran, Anatolia and the West, and had told the characteristics of this city attracts considerable attention. Therefore, it is important to explore the city of Baghdad with different perspectives of the travelers who describe Baghdad from various aspects. In this study, we will try to explain the city of Baghdad, where was the capital of the Abbasid Caliphate and one of the important history, science, culture, politics and commercial centers of the Islamic world. We will focus on the historical structure of Baghdad during both pre-Islamic and post-Islamic periods, and the changes that the city had undergone in the course of time up until today.
Baghdad in Travel Books
Keywords: Tarih; Din